ANALISIS PROFILE DAN KINERJA DEWAN PENGAWAS SYARIAH (DPS) PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) DI DAERAH ISTIMEWA YOGYAKARTA - Rif’an, Akhmad Arif (Syari'ah, 2018)
This study aims to analyze the profile and performance of the Sharia Supervisory Board (DPS) Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Specialties of Yogyakarta Special Region. DPS's duties and powers are the subject of this study. Population in this research is all DPS KSPPS in DIY. The sample size was 30 DPS with questionnaire instrument. Data analysis methods are used descriptively based on the results presented in the form of tabulation or tables, graphics or drawings and simple statistical figures. The results confirm that the formal education graduate profile of DPS shows that as much as 37.5% are Bachelor, 35% are Master, 7.5% are Doctoral 5%, Diploma and 15% are religious leaders. Profile of non-formal education graduates of DPS showed never attended sharia supervision training of 15% and 85% had never been. DPS also shall conduct operational oversight and make statements / opinions periodically in accordance with the provisions.